The The Effect of Interactive Mathematics Learning Media to Improve Students' Learning Independence - Pixyoriza Pixyoriza; Ridwan Ridwan; Uswatun Khasanah (CV. Edujavare Publishing, 2026)
Learning independence is one of the important abilities that students must have in learning mathematics. However, the level of student learning independence still needs to be improved through the use of innovative learning media. This study aims to determine the effect of interactive mathematics learning media on student learning independence. This study used a quantitative approach with a One Group Pretest–Posttest design. The research sample consisted of 15 students of the Mathematics Education Study Program, Nahdlatul Ulama University, Lampung. Data were collected using a learning independence questionnaire consisting of 25 statements. Data analysis included descriptive statistics, N-Gain, and Effect Size (Cohen's d). The results showed that all indicators of learning independence increased after the use of interactive learning media. The N-Gain value of 0.5198 is included in the moderate category, while the Effect Size value indicates a large influence. Thus, interactive mathematics learning media is effective for improving student learning independence.